DANGER «BAKONS» IDEAL OF SCIENCE - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The peculiaritiesof formation anddevelopment trend ofthe ideals andnorms, values of modern scientific knowledge.